Deletion of FtsH11 protease has impact on chloroplast structure and function in Arabidopsis thaliana when grown under continuous light. (19th September 2016) - Wagner, Raik; von Sydow, Lotta; Aigner, Harald; Netotea, Sergiu; Brugière, Sabine; Sjögren, Lars; Ferro, Myriam; Clarke, Adrian; Funk, Christiane
Abstract: The membrane‐integrated metalloprotease FtsH11 of Arabidopsis thaliana is proposed to be dual‐targeted to mitochondria and chloroplasts. A bleached phenotype was observed in ftsh11 grown at long days or continuous light, pointing to disturbances in the chloroplast. Within the chloroplast, FtsH11 was found to be located exclusively in the envelope. Two chloroplast‐located proteins of unknown function (Tic22‐like protein and YGGT‐A) showed significantly higher abundance in envelope membranes and intact chloroplasts of ftsh11 and therefore qualify as potential substrates for the FtsH11 protease. No proteomic changes were observed in the mitochondria of 6‐week‐old ftsh11 compared with wild type, and FtsH11 was not immunodetected in these organelles. The abundance of plastidic proteins, especially of photosynthetic proteins, was altered even during standard growth conditions in total leaves of ftsh11 . At continuous light, the amount of photosystem I decreased relative to photosystem II, accompanied by a drastic change of the chloroplast morphology and a drop of non‐photochemical quenching. FtsH11 is crucial for chloroplast structure and function during growth in prolonged photoperiod. Abstract : The membrane‐integrated metalloprotease FtsH11 of Arabidopsis thaliana was found to be located exclusively in the chloroplast envelope and to be crucial for chloroplast structure and function during growth in prolonged photoperiod. Two chloroplast‐located proteins of unknown function (Tic22‐like protein and YGGT‐A) showed significantly higher abundance in envelope membranes and intact chloroplasts of ftsH11 and therefore qualify as potential substrates for the FtsH11 protease.